Leadership Beyond the Schoolhouse: Preparing Principals to Engage in Advocacy (in Ethridge et al.'s "Advocacy in Education: Research-Based Strategies for Teachers, Administrators, and Teacher Educators") - Trombly, Christopher (2020)
Advocacy has become a crucial professional obligation for school principals. Seen by policymakers as honest brokers who have at heart the best interests of the children and families whom they serve, school principals should offer themselves to policymakers and their staffs as accessible and reliable sources of information about the actual or likely impacts of measures that have already been enacted or that are being introduced. They should be ready to collect, examine, and articulate data of interest to policymakers. Moreover, they should provide compelling stories for those policymakers to remember and retell as they debate, not only education-specific measures, but any policies impacting children’s ability to be healthy, safe, engaged, supported, and challenged.
Keywords: dept.edl

Report of the Task Force to Study the Comprehensive Needs of Children in the State - Trombly, Christopher (Connecticut General Assembly, 2022)

Learning in the time of COVID-19: capitalizing on the opportunity presented by the pandemic - Trombly, Christopher E. (Journal of Professional Capital and Community, 2020)
Purpose: This paper addresses the current disruption in the educational status quo ante that has been caused by the worldwide outbreak of COVID-19. Its purpose is to suggest how practicing educators, their professional associations and the university-based researchers with whom they partner might capitalize on the unanticipated opportunity to impact education policy that the pandemic presents. Design/methodology/approach: The author draws upon his own preparation and experiences – first as a long-time practitioner in the elementary and secondary school setting, then as a university professor – to offer insights and suggestions to practicing educators, their professional associations and the university-based researchers with whom they partner. Findings: Despite the unexpected challenges that the COVID-19 pandemic has presented to educators – challenges to which educators around the globe have risen admirably – the current crisis also affords practicing educators, their professional associations and the university-based researchers with whom they partner to change the status quo ante for the better. Originality/value: The particular value of this piece is twofold: its analysis of the impact of this unanticipated crisis upon education by an author who has served both in the elementary/secondary setting and at the university level, and its assertion that educators must avail themselves of this once-in-a-lifetime opportunity to change the educational status quo ante for the better. © 2020, Emerald Publishing Limited.
17 citations (Crossref) [2023-10-31] WOS:000546450400001
Keywords: Collaboration; Community; Professional judgment; dept.edl; peer-reviewed

Preparing principals for leadership beyond the schoolhouse - Trombly, Christopher E.; Griffith, D (Advocacy in Education: Research-Based Strategies for Teachers, Administrators, Parents, and the Community, 2020)
Keywords: dept.edl

Impact of supervision and evaluation on the professional development of school-based speech-language pathologists - Brown, Jacqueline; Trombly, Christopher; Roitsch, Jane (Perspectives of the ASHA Special Interest Groups, 2025)
Keywords: American Speech-Language-Hearing Association; Asha; Developmental psychology; Language development; Linguistics; Medical education; Medicine; Pedagogy; Professional development; Psychology; dept.edl

What’s COVID-19 Got to Do With It? Implementing the 2020 Connecticut Comprehensive School Counseling Framework - Trombly, Christopher E.; Parzych, Jennifer L.; Generali, Margaret M.; Yavuz, Olcay (Professional School Counseling, 2022)
The Connecticut Comprehensive School Counseling Framework was released in November 2020?8 months into the COVID-19 pandemic. The purpose of this mixed-methods study was to explore the progress made by principals and school counselors in implementing the new framework, and to understand the impact of the pandemic on their efforts to do so. We found significant overlap between the perceptions and priorities expressed by participating principals and school counselors. Particularly noteworthy was the fact that both groups described increased collaboration within their schools.
1 citations (Crossref) [2023-10-31]
Keywords: dept.csp; dept.edl; peer-reviewed

School Leadership for Learning: Learning Theory to Improve Professional Practice - Gregory, Jess L.; Ben-Avie, Michael; Billups, Felice; Grassetti, Mary; Hesser, Tiffany; Lawlor, Jennifer Lynne; Martone, Drey; Maykel, Cheryl; Minkos, Marlena L.; Paslov, Linda; Trombly, Christopher; Tucker, Lauren; et al. (Jess L. Gregory, 2021)
Keywords: Educational leadership; School administrators; Handbooks; manuals; etc; In-service training; School administrators; In-service training; Teachers; dept.edl; dept.sed; faculty_collection